Relationship of economies of scale (EOS) factors for Malaysian Industrialised building system (IBS) precast manufacturer - Tajul Ariffin, Syazwana (2019)
Industrialised Building System (IBS) or prefabrication has been identified as one of the key methods to reduce construction cost and gain financial benefits. The characteristic of controlled production and systematic process in the IBS manufacturing is helpful in quality production and profit generation. A structured financial guideline can assist IBS manufacturers to maximise the production of IBS components and gain competitive advantage. The economy of scale (EOS) is one of the available strategies for IBS manufacturers to reduce average cost and increase the level of production. However, many IBS manufacturers fail due to lack of understanding in EOS and limited of study in Malaysia. Therefore, this study has noted a gap of knowledge to examine the EOS for IBS manufacturers. This study aims to establish the EOS factors for precast manufacturers using quantitative method. In the first phase, a systematic literature review and interviews were used to assist and validate the collected factors. In the second phase, the questionnaire survey was conducted to collect data from the precast manufacturers. In the light of findings, 10 factors were noted significant and were further categorised into internal and external factors. The internal factors of EOS were technical, financial, labour, managerial, marketing, commerce, and core competence. While the external factors of precast manufacturers consist of risk bearing, external industry, and infrastructure factors. IBS manufacturers can use this study as a reference to assess the possibilities of their business expansion. The good combination of production factors (as can be referred to the framework of EOS factors for precast manufacturer) and existing mass production can effectively distribute the fixed cost and lead to economical production. In addition, the developed framework can assist the manufacturers in the development of planning and organising the operational process to sustain their business for a long period of time.